2019
DOI: 10.1039/c9ra00306a
|View full text |Cite
|
Sign up to set email alerts
|

TUG1 knockdown enhances adriamycin cytotoxicity by inhibiting glycolysis in adriamycin-resistant acute myeloid leukemia HL60/ADR cells

Abstract: Taurine-upregulated gene 1 (TUG1) has been reported as an oncogenic long non-coding RNA (lncRNA) in acute myeloid leukemia (AML).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…Among the other tested compounds, they showed a similar pattern inhibiting around 100% of the cell growth at the second-highest concentration, which does not occur with none of the tested concentrations of TAU. In addition, our result fit in with those obtained by Chen et al [ 63 ] who demonstrated that TAU up-regulate the taurine-upregulated gene 1 (TUG1) which serves an oncogenic role in the development of several tumors. Therefore, TAU would not be the responsible for the cytotoxic activity showed by CRB, being GLU one of the bioactive compounds involved in that effect.…”
Section: Discussionsupporting
confidence: 92%
“…Among the other tested compounds, they showed a similar pattern inhibiting around 100% of the cell growth at the second-highest concentration, which does not occur with none of the tested concentrations of TAU. In addition, our result fit in with those obtained by Chen et al [ 63 ] who demonstrated that TAU up-regulate the taurine-upregulated gene 1 (TUG1) which serves an oncogenic role in the development of several tumors. Therefore, TAU would not be the responsible for the cytotoxic activity showed by CRB, being GLU one of the bioactive compounds involved in that effect.…”
Section: Discussionsupporting
confidence: 92%
“…KCNQ1OT1 knockdown inhibited the proliferation, migration, and invasion of adriamycin‐resistant AML cells 39 . The Wnt/β‐catenin and PI3K/AKT/mTOR pathways are among the classic oncogenic pathways, and both are reported to be altered by dysregulated lncRNAs and involved in chemoresistance of leukemia 43,44,47 . Specifically, the lncRNA CRNDE was upregulated in AML patients treated with adriamycin‐based chemotherapy 44 .…”
Section: Roles Of Lncrnas In Resistance To Leukemia Treatmentsmentioning
confidence: 99%
“…Linc00239 induced chemoresistance and prevented doxorubicin‐induced cellular apoptosis by activating the PI3K/AKT/mTOR pathway 43 . TUG1 is another tumor‐promoting lncRNA that activated the AKT pathway in AML cells, and suppression of TUG1 could inactivate the AKT pathway to improve adriamycin cytotoxicity in AML cells 47 . Regarding tumor suppressors, the lncRNA HOTAIR can epigenetically suppress the tumor suppressor PTEN (methylation) via DNMT3b upregulation, thus promoting drug resistance in AML 48 …”
Section: Roles Of Lncrnas In Resistance To Leukemia Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…UCA1 promotes glycolysis by inhibiting the action of mRNA125a, which usually functions as a tumor suppressor but also appears to be involved in blocking HK-II (Sun et al, 2017), which in turn could participate in the stabilization of HIF1-α (Zhang et al, 2018). Also, thanks to its oncogenic role, the increase in the expression of the LncRNA TUG1 (taurine-upregulated gene 1) is accompanied by the increase in the expression of the mRNAs of HK-II and PKM2 in HL60 cells resistant to doxorubicin (HL60/DOX) (Chen L. et al, 2019a). Another LncRNA, HOTAIRM1 (HOX transcript antisense intergenic RNA myeloid-specific 1), involved in myeloid lineage maturation and overexpressed in AML, has been compromised by resistance to Ara-C. Its deletion has been reported to improve drug activity and decrease glucose consumption and therefore lactate production, mainly mediated by the reduction of PFKP in HL60/WT and THP-1/WT cells (Chen et al, 2020).…”
Section: Figurementioning
confidence: 99%